2018
DOI: 10.1037/dec0000081
|View full text |Cite
|
Sign up to set email alerts
|

The effect of goals and environments on human performance in optimal stopping problems.

Abstract: In optimal stopping problems, people are asked to choose the best option out of a sequence of alternatives, under the constraint that they cannot return to an earlier option once it is rejected. We examine human performance on variations of the optimal stopping problem, with different environments and with different goals. Specifically, we consider environments that have relatively high or low numbers, under the goals of choosing the maximum or the minimum. A natural consequence of this design is that we study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…Information about the distribution was also conveyed to participants in a study by Rapoport and Tversky (1970), in which seven individual participants viewed an impressive 15,600 draws from probability distributions over several weeks before playing secretary problem games with values drawn from the same distributions. In a study where participants played secretary problem games on five values drawn from either a left-skewed or a right-skewed distribution, Guan and Lee (2017) provided information about the distribution by requiring participants to first play eight "practice problems" before beginning the main part of the experiment. These investigations are similar to our study in that they both involve repeated play and that they present players with actual values instead of ranks.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Information about the distribution was also conveyed to participants in a study by Rapoport and Tversky (1970), in which seven individual participants viewed an impressive 15,600 draws from probability distributions over several weeks before playing secretary problem games with values drawn from the same distributions. In a study where participants played secretary problem games on five values drawn from either a left-skewed or a right-skewed distribution, Guan and Lee (2017) provided information about the distribution by requiring participants to first play eight "practice problems" before beginning the main part of the experiment. These investigations are similar to our study in that they both involve repeated play and that they present players with actual values instead of ranks.…”
Section: Related Workmentioning
confidence: 99%
“…First, to our knowledge, our study is the first study to begin with an unknown distribution that players can learn over the course of the experiment. Previous studies have provided rank information only (e.g., Seale and Rapoport 1997), given a full description of the distribution (leaving no scope for learning) (e.g., Lee 2006), or presented samples from the distribution to the participants before the main experiment (e.g., Tversky 1970, Guan andLee 2017). Seemingly small differences in instructions to participants could have a large effect.…”
Section: Conclusion: Behavioral Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have investigated tasks closer to real sequential choice problems by presenting the actual value of the option to the decision makers (Guan & Lee, 2017;Guan, Lee, & Vandekerckhove, 2015;Kogut, 1990;Lee, 2006;Shu, 2008;von Helversen & Mata, 2012). In this version, the optimal solution is based on calculating the expected reward of the remaining outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…From this expected reward, a threshold is calculated for each option in the sequence as described by Gilbert and Mosteller (Gilbert & Mosteller, 1966). Results showed that human behavior was systematically biased away from the optimal threshold (Guan & Lee, 2017;Guan et al, 2015;Lee, 2006). Furthermore, these studies still kept the restriction that only the best alternative is rewarded-a payoff function that does not correspond well with everyday experiences.…”
Section: Introductionmentioning
confidence: 99%